Enhancement of β-Globin Gene Expression in Thalassemic IVS2-654 Induced Pluripotent Stem Cell-Derived Erythroid Cells by Modified U7 snRNA. (18th February 2017) - Phanthong, Phetcharat; Borwornpinyo, Suparerk; Kitiyanant, Narisorn; Jearawiriyapaisarn, Natee; Nuntakarn, Lalana; Saetan, Jirawat; Nualkaew, Tiwaporn; Sa-ngiamsuntorn, Khanit; Anurathapan, Usanarat; Dinnyes, Andras; Kitiyanant, Yindee; Hongeng, Suradej
Abstract: The therapeutic use of patient-specific induced pluripotent stem cells (iPSCs) is emerging as a potential treatment of β-thalassemia. Ideally, patient-specific iPSCs would be genetically corrected by various approaches to treat β-thalassemia including lentiviral gene transfer, lentivirus-delivered shRNA, and gene editing. These corrected iPSCs would be subsequently differentiated into hematopoietic stem cells and transplanted back into the same patient. In this article, we present a proof of principle study for disease modeling and screening using iPSCs to test the potential use of the modified U7 small nuclear (sn) RNA to correct a splice defect in IVS2-654 β-thalassemia. In this case, the aberration results from a mutation in the human β-globin intron 2 causing an aberrant splicing of β-globin pre-mRNA and preventing synthesis of functional β-globin protein. The iPSCs (derived from mesenchymal stromal cells from a patient with IVS2-654 β-thalassemia/hemoglobin (Hb) E) were transduced with a lentivirus carrying a modified U7 snRNA targeting an IVS2-654 β-globin pre-mRNA in order to restore the correct splicing. Erythroblasts differentiated from the transduced iPSCs expressed high level of correctly spliced β-globin mRNA suggesting that the modified U7 snRNA was expressed and mediated splicing correction of IVS2-654 β-globin pre-mRNA in these cells. Moreover, a less active apoptosis cascade process was observed in the corrected cells at transcription level. This study demonstrated the potential use of a genetically modified U7 snRNA with patient-specific iPSCs for the partial restoration of the aberrant splicing process of β-thalassemia.